TEACHERS’ PERCEPTION OF 2013 CURRICULUM IMPLEMENTATION IN JUNIOR HIGH SCHOOL - Pane, Isli Iriani Indiah; Hutasuhut, Mahmud Layan; Damanik, Sisila Fitriany; Haswani, Fahri (Universitas Islam Sumatera Utara (UISU), 2022)
The aim of this study was to examine English teachers’ perceptions and concerns about the implementation of the2013 curriculum in Junior high school in Indonesia. This study reports findings from interpretive case study design in a private junior high school in Medan region, Indonesia with 2 teachers. Data were generated using questionnaires, focus group interview, classroom observation and documentation. The research focus was on how the English teachers have implemented the 2013 curriculum. The findings indicate that the implementation of the curriculum was still problematic due to the teachers’ lack of knowledge of the 2013 curriculum and the teachers’ pile of work. In addition, one of the teachers was still confused with the implementation of the 2013 curriculum, to work with teenagers’ students, overcrowded classrooms, learning environments, and insufficient teaching and learning materials and facilities. This study recommends that to improve the current situation and attain quality provision of junior high schools, teachers need to develop their professional knowledge through socialization and the in-service training. The government policy planners need to provide initial teacher education that suit junior high school contexts, professional development, and conducive teaching and learning environments with available resources for effective teaching and learning practices.